2021
DOI: 10.1080/23311975.2021.1900500
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the impact of ESG on financial performance of FTSE350 UK firms: Static and dynamic panel data analysis

Abstract: This study re-examines the impact of ESG (economic, environmental, social, and corporate governance performance) on the financial performance of UK firms. Most recent sample of 351 firms from FTSE350 for the time period 2002-2018 is used. The study estimates the impact of total ESG and individual dimensions of ESG on corporate financial performance using static and dynamic panel data techniques, and it also examines the impact of high and low ESG on firm financial performance. Further, the study investigates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 45 publications
(49 reference statements)
6
49
2
1
Order By: Relevance
“…However, this negative relationship between ESG scores and average returns seems to be more consistent for Europe than for the US. These findings are in line with Ahmad et al [54], who studied the relationship between ESG and financial performance of the FTSE350 for the time period between 2002 and 2018 and found that "firm size moderates the relationship between ESG performance and financial performance". We also conduct this investigation using Thomson Reuters Refinitiv ESG Scores and find similar results for the positive relationship between ESG and market capitalization.…”
Section: Datasupporting
confidence: 90%
“…However, this negative relationship between ESG scores and average returns seems to be more consistent for Europe than for the US. These findings are in line with Ahmad et al [54], who studied the relationship between ESG and financial performance of the FTSE350 for the time period between 2002 and 2018 and found that "firm size moderates the relationship between ESG performance and financial performance". We also conduct this investigation using Thomson Reuters Refinitiv ESG Scores and find similar results for the positive relationship between ESG and market capitalization.…”
Section: Datasupporting
confidence: 90%
“…Ahmad et al (2021), this paper explores the impact of threedimensions of ESG, namely, OESG, IESG, and SIESG as the independent variables on energy-adjusted firm efficiency, as the existing literature rarely comprehensively discusses the impact of the three pillars of ESG in the same sample. In addition, the literature scarcely delves into what fuels the ESG pillars behind the presentation of established impacts.…”
mentioning
confidence: 99%
“…In addition, we base our analyses on U.S. data due to the availability of reliable data for a long interval, which is critical to our methodology. However, Ahmad et al ( 2021 ), Duque-Grisales and Aguilera-Caracuel ( 2019 ), and Johnson et al ( 2019 ) showed that the relationship between financial performance and ESG performance differs across countries. Therefore, future research is needed to determine how these relationships vary across countries.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses (e.g., Busch & Friede, 2018 ) concluded that social and environmental responsiveness positively affects financial performance. Other studies find differences in the role of ESG in explaining corporate financial performance; namely, social responsibility is a driver of financial performance whereas environmental and governance performance do not affect financial performance (Ahmad et al, 2021 ; Tanin et al, 2019 ).…”
Section: Corporate Sustainable Development Indicators: Hypothesesmentioning
confidence: 99%